Bridging the digital divide, aiming to become lifelong learners - Kachelhoffer, A.; Khine, Myint Swe (2009)
Studies in the past documented that proper use of Information and Communication Technology (ICT) can positively impact learning. It has been shown that the use of ICT can help students develop inquiry and thinking skills, increase learning opportunities, enhance learning activities, and improve learning outcomes for students. While there are bright prospects, barriers still exist in certain areas, particularly the readiness of the teachers who will adopt the technology, administrative support and technology infrastructure in schools. This study reports the patterns of computer use and computer self-efficacy among students in a postgraduate degree in education program in the UAE. The survey from 91 students were analysed and found that most students have positive attitudes and beliefs in ICT, but lacking behind the use of such technologies. The authors suggest that it is necessary to create opportunities for them to use ICT in the classroom and further develop knowledge and skills in Web 2.0 technologies. © IFIP International Federation for Information Processing 2009.